Comparison of inhibitory effects and mechanisms of lactonic sophorolipid on different pathogenic bacteria - Ma, Xiao-jing; Wang, Tong; Zhang, Hui-min; Shao, Jun-qian; Jiang, Mei; Wang, Huai; Zhu, Hui-xia; Zhou, Dong (Frontiers in Microbiology, 2022)
Crude sophorolipids (SLs) have been proven to perform varying degrees of inhibitory effects on different pathogenic bacteria. However, systematic comparative studies of pure lactonic sophorolipid (LSL) among different types of bacteria are few. In this study, the antibacterial effects and mechanisms of LSL on pathogenic bacteria of Staphylococcus aureus, Lactobacillus sp., Pseudomonas aeruginosa, and Escherichia coli were investigated. Bacteriostatic circle, antibacterial rate, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) of LSL on different pathogenic bacteria were measured. Then, the antibacterial mechanisms of LSL on S. aureus and P. aeruginosa were explored using ultrastructural observation, cell membrane permeability analysis, intracellular ATP content determination, and extracellular UV absorption detection. With the minimum MIC and MBC values of 0.05 and 0.20 mg/ml, LSL exhibited the best inhibitory effect against S. aureus, followed by P. aeruginosa. LSL showed no significant inhibitory effect on E. coli and Lactobacillus sp. For both S. aureus and P. aeruginosa, LSL achieved bacteriostatic and bactericidal effects by destroying the cell wall, increasing the permeability of the cell membrane and leading to the flow out of intracellular contents. However, the action mode and action intensity of LSL on the cell wall and membrane of these two bacteria were significantly different. LSL had a greater influence on the cell membrane of S. aureus by “leaking,” while it exhibited a stronger effect on the cell wall of P. aeruginosa by “blasting.” These results contributed to a better understanding of the relationship between LSL and different bacterial cell structures, further suggesting the conclusion that LSL might be used for the targeted treatment of special pathogenic bacteria.